Recurrence Prediction Score of the Localy Advance Breast Cancer in West Sumatera Province, Indonesia - Shinta Qorina; Wirsma Arif Harahap; Ricvan Dana Nindrea (HM Publisher, 2021)
Introduction: Breast cancer is the most common malignancy that occurs in women in the world, which is about 18% of cancer cases that occur in women. Every year there are 1 million new cases of breast cancer worldwide and nearly 60,000 patients die from this disease. Therefore, the authors want to find out more about the prognosis factors that play a role in influencing the survival of patients with locally advanced breast cancer in Padang city, West Sumatera Province Indonesia. Methods: This study is a retrospective case-control study of locally advanced breast cancer for patients in Padang city. The study was conducted at the Surgical Oncology Division of Dr. M Djamil Padang Hospital, Ropana Suri Hospital, Ibnu Sina Hospital and Siti Rahmah Padang Hospital from September 2018 to December 2018. The total number of samples for the two groups was 242 people. The sampling technique used was convenience sampling. Results: In this study 4 prognostic factors were found that had a significant effect on predicting breast cancer recurrence, namely histopathological type, stage, regional lymph and lymphovascular invasion with p <0.05. Conclusion: Prognosis factors that influence breast cancer recurrence are histopathological type, stage, regional lymph node status and lymphovascular invasion. A scoring system is obtained that is good enough to predict the possibility of breast cancer recurrence.